Using latent class analysis to identify clinical features of patients with occlusive myocardial infarction: Preangiogram prediction remains difficult. Issue 2 (8th February 2022) - Knoery, Charles; McEwan, Katie. A.; Manktelow, Matthew; Watt, Jonathan; Smith, Jamie; Iftikhar, Aleeha; Rjoob, Khaled; Bond, Raymond; McGilligan, Victoria; Peace, Aaron; McShane, Anne; Heaton, Janet; et al.
Abstract: Background: Treatment decisions in myocardial infarction (MI) are currently stratified by ST elevation (ST‐elevation myocardial infarction [STEMI]) or lack of ST elevation (non‐ST elevation myocardial infarction [NSTEMI]) on the electrocardiogram. This arose from the assumption that ST elevation indicated acute coronary artery occlusion (OMI). However, one‐quarter of all NSTEMI cases are an OMI, and have a higher mortality. The purpose of this study was to identify features that could help identify OMI. Methods: Prospectively collected data from patients undergoing percutaneous coronary intervention (PCI) was analyzed. Data included presentation characteristics, comorbidities, treatments, and outcomes. Latent class analysis was undertaken, to determine patterns of presentation and history associated with OMI. Results: A total of 1412 patients underwent PCI for acute MI, and 263 were diagnosed as OMI. Compared to nonocclusive MI, OMI patients are more likely to have fewer comorbidities but no difference in cerebrovascular disease and increased acute mortality (4.2% vs. 1.1%; p < .001). Of OMI, 29.5% had delays to their treatment such as immediate reperfusion therapy. With latent class analysis, while clusters of similar patients are observed in the data set, the data available did not usefully identify patients with OMI compared to non‐OMI. Conclusion: Features between OMI and STEMI are broadly very similar. However, there was no difference in age and risk of cerebrovascular disease in the OMI/non‐OMI group. There are no reliable characteristics therefore for identifying OMI versus non‐OMI. Delays to treatment also suggest that OMI patients are still missing out on optimal treatment. An alternative strategy is required to improve the identification of OMI patients.